Dependencia a las redes sociales y el rendimiento académico en los niños de Educación General Básica - Lopez Lopez, Paola Tatiana (2024)
The main objective of this research is to analyze how dependence on social networks affects students' academic performance in the seventh year of primary education. This study sought to infer bibliographically the effects of time and attention devoted to social networks on children's academic performance. A qualitative approach was used to address the research objective, complemented with quantitative techniques; it is framed in a non-experimental design, with a Diagnostic-Exploratory and Descriptive type of research. Surveys were applied to 25 students to evaluate their patterns of use of social networks and their effects on academic performance. In addition, an interview was conducted with the tutor teacher to obtain additional perspectives on the topic. The data collected were analyzed using descriptive statistics to identify key trends and correlations. The research results revealed that most students prefer using mobile devices over books, with 68% of respondents. Regarding social networking activities, 72% of students indicated they spend most of their time watching videos. TikTok and WhatsApp were the most used platforms. The research also found that 44% of students spend more than four hours daily on social networks, suggesting a high dependence. Through analysis of the literature, it is determined that excessive use affects students' ability to concentrate on their tasks, with 48% indicating that they cannot concentrate while they have social networks open. From the teacher's perspective, it is observed that the intensive use of social networks contributes to the lack of compliance with school activities and less attention to classes. In addition, an analysis of academic performance was conducted to determine whether social networks have a negative influence, resulting in a significant influence of social networks on academic performance.